substitution method

chelle

New member
Joined
May 28, 2012
Messages
3
x+y=48
2y-x=48
Okay so there are steps to follow is this the right start?
x+y=48
x+y-x=48-x
x=48-x
now where to???
 
x+y=48
2y-x=48
Okay so there are steps to follow is this the right start?
x+y=48
x+y-x=48-x
x=48-x
now where to???

That should be y = 48 - x, not x=48-x.

Since you have solved the first equation in terms of y, you can now substitute into the second equation:

2y-x=48
2(48 - x) - x = 48

You now have an equation with only one variable in it, and you can now solve for that variable. Continue.
 
Top